Sustainability through the Lens of Environmental Sociology - Md Saidul Islam (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Our planet is undergoing radical environmental and social changes. Sustainability has now been put into question by, for example, our consumption patterns, loss of biodiversity, depletion of resources, and exploitative power relations. With apparent ecological and social limits to globalization and development, current levels of consumption are unsustainable, inequitable, and inaccessible to the majority of humans. Understanding and attaining sustainability is a crucial matter at a time when our planet is in peril-environmentally, economically, socially, and politically. Since its official inception in the 1970s, environmental sociology has provided a powerful lens to understanding the challenges, possibilities and modes of sustainability. Most chapters in this book were published as peer-reviewed articles in Sustainability in its special issue "Sustainability through the Lens of Environmental Sociology", providing an environmental sociology approach to understanding and achieving the widely used notion of "sustainability." This edited collection covers, among other topics, the inherent discursive formations of environmental sociology, conceptual tools and paradoxes, competing theories and practices, and their complex implications on our society at large. Chapters in this book specifically focus on how sustainable development has been understood through different theoretical lenses in environmental sociology, such as ecological modernization, policy/reformist sustainable development, and critical structural approaches (such as the treadmill of production, ecological Marxism, metabolic rift theory, etc.); and how sustainable development has been practiced in, or by, various stakeholders, such as states, corporations, and local communities, for various ends, through the use of specific case studies, showing, for example, the discursive shifts, dynamic formations, and diverse contours of sustainable development. The range of relevant topics includes: • Environmental sociology as a field of inquiry for sustainability • Historical context of sustainable development in environmental sociology • Nature-society relationship in environmental sociology • Theories/approaches to sustainability discourse in environmental sociology • Environmentalism/environmental movements for sustainability • Empirical cases (such as climate change, biodiversity, food, certification, etc.) through the lens of environmental sociology